2015
DOI: 10.1093/rheumatology/kev204
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated antigens in systemic sclerosis patients with interstitial lung disease: association with lung involvement and cancer risk

Abstract: TAAs can be elevated in the sera of SSc patients and correlate with the degree of lung damage, suggesting a role as severity biomarkers. Close follow-up is necessary in SSc patients because of the increased cancer risk overall in patients with increased TAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
2
14
1
9
Order By: Relevance
“…B is classified as a Group 1 carcinogen to humans and animals by the International Agency for Research on Cancer (IARC), but its role in the development of cancer in scleroderma patients should be further investigated in other studies. Interestingly, patients with diffuse skin disease have a higher risk of cancer compared to other scleroderma patients and, as seen from our results, these patients are exposed to higher B concentrations [ 21 ].…”
Section: Discussionmentioning
confidence: 69%
“…B is classified as a Group 1 carcinogen to humans and animals by the International Agency for Research on Cancer (IARC), but its role in the development of cancer in scleroderma patients should be further investigated in other studies. Interestingly, patients with diffuse skin disease have a higher risk of cancer compared to other scleroderma patients and, as seen from our results, these patients are exposed to higher B concentrations [ 21 ].…”
Section: Discussionmentioning
confidence: 69%
“…36 In a study performed by Celeste et al 37 on 221 SSc patients, among which 168 with ILD, CA15-3 serum levels were found to correlate with the extent of fibrosis detected on HRCT as well as to be predictive for progression-free survival, with progression being defined by a decline in either FVC or DLCO. Supporting these data, De Luca et al 38 found that high CA15-3 levels were associated with lower FVC and higher interstitial and alveolar scores and were predictive for a short-term decline in lung function in 80 SSc-ILD patients. Despite the promising data, CA15-3 needs further systematic evaluation as a predictive biomarker, especially concerning its applicability in non-European cohorts.…”
Section: Surfactant Protein-dmentioning
confidence: 83%
“…SSc ve SLE akciğer tutulumunda CA-15-3 seviyesinin arttiği gösterilmiştir [4,5]. Yapilan bir çalişmada serum CA15-3 seviyesinin poliartrit, ANA pozitifliği ve serum CRP düzeyleri ile ilişkili olduğu gösterilmiştir [5].Serum CA-15-3 seviyesi, idiyopatik pulmoner fibrozis/ interstisyel pnömoni tanili hastalarda yüksek bulunabilir [9]. Bir çalişmada SSc-intersitisyel akciğer hastaliğinda biyolojik belirteç olarak CA-15-3'ün olasi rolü üzerinde durulmuştur.…”
Section: Discussionunclassified
“…Bu belirteç, akciğer hasarinin derecesini belirlemede ve akciğer tutulumunun prognozunda klinik olarak anlamli değişikliklerin gösterilmesinde iyi bir özgüllük ve duyarlilik sunmuştur [10]. İnterstisyel akciğer hastaliği olan SSc tanili hastalarda serum CA-15-3 seviyeleri ile yüksek çözünürlüklü BT puanlamasi arasinda güçlü bir korelasyonolduğu bulunmuştur [9,10].…”
Section: Discussionunclassified